2003
DOI: 10.1124/jpet.103.052514
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitors Activate Septohippocampal GABAergic Neurons via Muscarinic but Not Nicotinic Receptors

Abstract: Acetylcholinesterase (AChE) inhibitors, which increase synaptic levels of available acetylcholine (ACh) by preventing its degradation, are the most extensively prescribed drugs for the treatment of Alzheimer's disease. In animals, AChE inhibitors improve learning and memory, reverse scopolamine-induced amnesia, and produce hippocampal theta rhythm. The medial septum/diagonal band of Broca (MSDB), which maintains hippocampal theta rhythm and associated mnemonic functions via the septohippocampal pathway, is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 42 publications
5
33
0
Order By: Relevance
“…Thus, , which is a conjugate of the fluorochrome Cy3, and an antibody (Ab) against the p75 receptor (192IgG), is taken up only by cholinergic terminals and thus selectively labels only the cholinergic subpopulation. The specificity of this marker and its inert nature have been thoroughly confirmed in previous studies by us Wu et al, 2000Wu et al, , 2003b and by others (Hartig et al, 1998).…”
Section: Methodssupporting
confidence: 69%
“…Thus, , which is a conjugate of the fluorochrome Cy3, and an antibody (Ab) against the p75 receptor (192IgG), is taken up only by cholinergic terminals and thus selectively labels only the cholinergic subpopulation. The specificity of this marker and its inert nature have been thoroughly confirmed in previous studies by us Wu et al, 2000Wu et al, , 2003b and by others (Hartig et al, 1998).…”
Section: Methodssupporting
confidence: 69%
“…The mGluR1a has been shown to lie upstream of PLC-␤4 in the medial septum (Nakamura et al, 2004), and mGluR1a antagonists have been shown to decrease the firing rate of both septohippocampal cholinergic and GABAergic neurons in the medial septum (Wu et al, 2003a(Wu et al, , 2004. Interestingly, acetycholinesterase inhibitors have been shown to not only increase the acetylcholine concentration in the hippocampus (Van Dam et al, 2005;Cerbai et al, 2007) but also to enhance GABAergic neuronal firing rate in the medial septum (Wu et al, 2003b). Therefore, administration of an acetylcholine esterase inhibitor to PLC-␤4 Ϫ/Ϫ mice might be expected to recover attenuated cholinergic theta rhythms in the mutant.…”
Section: Discussionmentioning
confidence: 99%
“…To further confirm the interrelationship between cholinergic theta rhythms and anxiety behavior, we designed an experiment to determine whether increasing cholinergic transmission in PLC-␤4 Ϫ/Ϫ mice could rescue the attenuated amplitude of cholinergic theta rhythms, and thereby normalize the attendant anxiety behavior. To this end, we administered the cholinergicenhancing drug, rivastigmine, an acetylcholinesterase inhibitor known to increase the cholinergic transmission in the septohippocampal pathway (Wu et al, 2003b;Van Dam et al, 2005;Cerbai et al, 2007).…”
Section: Rescue Of the Plc-␤4mentioning
confidence: 99%
“…This lack of adaptation in the hippocampal cholinergic response may be due to the loss of MS/DB cells in the PTD model. There is evidence that both cholinergic and GABAergic cells in the MS/DB modulate neural activation of the hippocampus [1,56,60]. Cholinergic activation in the hippocampus triggers rhythmic activity that can persist for hours and such rhythmic activity is related to both learning and neural plasticity [11].…”
Section: Discussionmentioning
confidence: 99%